2022
DOI: 10.1371/journal.pone.0267747
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing acute stroke outcome prediction models: Comparison of generalized regression neural networks and logistic regressions

Abstract: Background Generalized regression neural network (GRNN) and logistic regression (LR) are extensively used in the medical field; however, the better model for predicting stroke outcome has not been established. The primary goal of this study was to compare the accuracies of GRNN and LR models to identify the most optimal model for the prediction of acute stroke outcome, as well as explore useful biomarkers for predicting the prognosis of acute stroke patients. Method In a single-center study, 216 (80% for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Qu et al studied 216 patients with acute stroke who were admitted to the Shenzhen Second People's Hospital between December 2019 to June 2021 [5]. They compared the accuracies of generalized regression neural networks and logistic regression models to identify an optimal model for predicting acute stroke outcomes.…”
Section: Desi̇gn and Setti̇ngmentioning
confidence: 99%
See 4 more Smart Citations
“…Qu et al studied 216 patients with acute stroke who were admitted to the Shenzhen Second People's Hospital between December 2019 to June 2021 [5]. They compared the accuracies of generalized regression neural networks and logistic regression models to identify an optimal model for predicting acute stroke outcomes.…”
Section: Desi̇gn and Setti̇ngmentioning
confidence: 99%
“…The outcome variable was the Barthel Index (BI) on discharge. It was reported that the generalized regression neural network showed a better performance than the logistic regression [5]. The primary study was approved by the Ethics Committee of Shenzhen Second People's Hospital.…”
Section: Desi̇gn and Setti̇ngmentioning
confidence: 99%
See 3 more Smart Citations